2007
DOI: 10.1002/ajmg.b.30576
|View full text |Cite
|
Sign up to set email alerts
|

The BDNF Val66Met × 5‐HTTLPR × child adversity interaction and depressive symptoms: An attempt at replication

Abstract: Kaufman et al. [2006] reported a higher order interaction effect between specific genetic and environmental factors in a model of depressive symptoms, requiring independent replication. BDNF Val(66)Met and 5-HTTLPR genotypes were determined in female participants pertaining to a large ongoing twin study. Participants also filled in questionnaires on childhood adversity and depressive symptoms. Two- and three-way interactions between genetic polymorphisms and early adversity were examined in models of depressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
5
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 11 publications
9
113
5
3
Order By: Relevance
“…This conclusion is in accordance with recent experimental and meta-analytic studies suggesting that some polymorphisms may not directly modulate vulnerability to depression, but may be components in the modulation of more general behaviour phenotypes via complex interactions of endoenvironments or endophenotypes (gene-gene interactions) with positive and negative exoenvironments (Feder et al, 2009;Kaufman et al, 2006;Uher & McGuffin, 2008;Wichers et al, 2008b). Moreover, the genome may be programmed by epigenetic mechanisms driven by interactions between an individual and their environment over their lifespan (Szyf, McGowan, & Meaney, 2007).…”
Section: Some Potential Multi-level Mechanisms Conferring Resiliencesupporting
confidence: 90%
“…This conclusion is in accordance with recent experimental and meta-analytic studies suggesting that some polymorphisms may not directly modulate vulnerability to depression, but may be components in the modulation of more general behaviour phenotypes via complex interactions of endoenvironments or endophenotypes (gene-gene interactions) with positive and negative exoenvironments (Feder et al, 2009;Kaufman et al, 2006;Uher & McGuffin, 2008;Wichers et al, 2008b). Moreover, the genome may be programmed by epigenetic mechanisms driven by interactions between an individual and their environment over their lifespan (Szyf, McGowan, & Meaney, 2007).…”
Section: Some Potential Multi-level Mechanisms Conferring Resiliencesupporting
confidence: 90%
“…Determining the basis for this vulnerability is of key importance. Though nascent, the literature examining this topic suggests that early-life stress and BDNF genotype may interact to result in depression [120]. A recent study of 1,435 adults with a history of MDD reported that the experience of recent life stressors is associated with decreased levels of BDNF [121].…”
Section: Neurobiological Factorsmentioning
confidence: 99%
“…A single nucleotide polymorphism in the gene encoding brain-derived neurotrophic factor (BDNF) has been shown to interact with the 5-HTTLPR on molecular and system level 18 and to further strengthen the G Â E between 5-HTTLPR and environmental adversity in epidemiological studies. 16,19,20 Specifically, human epidemiological studies indicate that BDNF 66met allele interacts with the 5-HTTLPR short allele to confer sensitivity to positive and negative environmental factors. This three-way interaction may be especially relevant to the treatment of depression as BDNF has been shown to mediate the effects of antidepressants, including those acting on the serotonin transporter.…”
Section: The Interacting Causes Of Depressionmentioning
confidence: 99%